KAJIAN KESESUAIAN LINGKUNGAN DAN EKONOMI BUDIDAYA IKAN GURAMI (Osphronemus gouramy) DI DESA PINANG SEBATANG, KECAMATAN SIMPANG KATIS, KABUPATEN BANGKA TENGAH - Mega Juni; Robin Robin; Endang Bidayani (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
Cultivation is an activity that is carried out in connection with the process of multiplaying resources, one of which is in the field of fisheries. This activity, especially freshwater cultivation, has developed in the community, especially in Bangka Belitung Province, but the ponds used suitability the requirements of both physical, chemical and biological parameters of the waters as well as business feasibility. This study to knew suitability of water quality and analyze the cultivation of gourami in Pinang Sebatang Village. This research was carried out in December 2020 in Bangka Tengah district. This study used a survey method in the form of a case study methode in determining water quality. And then carried out a feasibility test of water quality using the STRORET method and the census method to analyzing cultivation business. Water quality and business analysis were carried out in the gourami cultivators’ pond at Pinang Sebatang Village sustainable. The result showed that the water quality in the gourami aquaculture pond at Pinang Sebatang Village was categorized as moderately polluted water quality status in pond 1 with a score of -12 and the status with lightly polluted in pond 2 with a score of -2. The method of data processing analysis of gourami cultivation at Pinang Sebatang Village uses quantitative methods. The result of the study showed that the income per cycle was Rp 120.000.000,00, income per cycle of Rp. 49.368.000,00, profit per cycle of Rp 38.568.000,00 and business efficiency of 1,69. Form the result of the STORET analysis and the business analysis that has been obtained, the cultivation pond at the Pinang Sebatang Village is feasible to be developed for the cultivation of gourami rearing.